Enrolling Caregivers in Obesity Interventions to Improve Obesity-Related Outcomes in Children. (October 2022) - Bessette, Hannah; Song, MinKyoung; Lyons, Karen S.; Stoyles, Sydnee; Lee, Christopher S.; Hansen, Lissi; Winters-Stone, Kerri
In this study, we assessed the influences of change in moderate-to-vigorous physical activity (MVPA)/sedentary time (ST) of caregivers participating in a commercial weight-loss program on their children's change in MVPA/ST. Data from 29 caregivers and their children were collected over 8 weeks. We used multivariable linear regression to assess associations of changes in caregiver's percent of time spent in MVPA/ST and changes in their child's percent of time spent in MVPA/ST. For caregivers that decreased body mass index (BMI) over 8 weeks, changes in caregivers' MVPA was strongly associated with the change in children's MVPA (β = 2.61 [95% CI: 0.45, 4.77]) compared to caregivers who maintained/increased BMI (β = 0.24 [–2.16, 2.64]). Changes in caregivers' ST was strongly associated with changes in children's ST (β = 2.42 [1.02, 3.81]) compared to caregivers who maintained/increased BMI (β = 0.35 [–0.45, 1.14]). Findings reinforce encouraging caregivers to enroll in weight-loss programs for the benefit of their children as well as for themselves.